ANALISIS KEBUTUHAN PELATIHAN KARYAWAN DALAM PENINGKATAN KINERJA DI DPMPTSP KARAWANG - Lulu Kamelia; Dedi Mulyadi; Sungkono Sungkono (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to analyze employee training needs in improving performance at the Karawang Investment and One-Stop Integrated Service Office (DPMPTSP). Using qualitative methods with in-depth interviews and observations, the research identifies three main skill areas needed: mastery of management information systems, effective communication skills, and understanding of current regulations. Performance analysis shows that 85% of employees meet or exceed work targets, with generally good team performance. The results reveal a strong positive relationship between participation in needs-based training and performance improvement. Based on these findings, a comprehensive training program is recommended, covering information systems training, effective communication, regulatory updates, and investment project management. The implementation of these recommendations is projected to significantly improve service efficiency and investor satisfaction in the long term.